Aleitamento materno de prematuros em hospital amigo da criança: da alta hospitalar ao domicílio - Ana Leticia Monteiro Gomes; Talita Balaminut; Silvia Braña Lopez; Karla de Araújo do Espírito Santo Pontes; Carmen Gracinda Silvan Scochi; Marialda Moreira Christoffel (Universidade Federal do Ceará, 2017)
Objective: to verify the prevalence of breastfeeding of preterm infants in neonatal units. Methods: an exploratory, cross-sectional study was performed at a Child-Friendly Hospital with 21 premature infants and their mothers. Interviews and a survey of medical records were performed using a form to collect data, which were analyzed through descriptive statistics. Results: the onset of milk feeding and breastfeeding was, respectively, 61.7 hours and 17.2 days on average. At hospital discharge, 47.6% of the preterm infants were breastfed; 47.6% were on exclusive breastfeeding; and 4.8% were on artificial milk feeding. At home, there were no changes in feeding patterns at seven to fifteen days after hospital discharge. Conclusion: it is necessary to strengthen actions for promotion, protection and support that encourage the practice of breastfeeding.